Comparison of conventional techniques and higher imaging modalities in the evaluation of relation between the third molar and inferior alveolar nerve canal: A pilot study - Vathsala Patil; Keerthilatha M Pai; R Vineetha; K V Rajagopal; Winniecia Dkhar (Wolters Kluwer Medknow Publications, 2019)
Context: Mandibular third molars are the most commonly impacted teeth, and their surgical removal can be associated with inferior alveolar nerve (IAN) injury. To avoid the deleterious complication of nerve injury on patients, a thorough visualization of IAN and its localization are essential. Aims and Objectives: The aims and objectives of this study were to evaluate the efficacy of two conventional localization techniques in determining the relationship of mandibular third molars to IAN and to assess its reliability in comparison with computed tomography (CT). Settings and Design: Panoramic radiograph (PR) was taken using Kodak 8000C Digital Panoramic and Cephalometric system. Intraoral periapical radiographs (IOPAs) were taken using Kodak 2200 Intraoral X-ray machine. CT scan images were taken using multidetector CT scans. Materials and Methods: Two IOPAs (0° and −20° vertical angulation) and PR and CT scan images of thirty mandibular third molars were taken. Two combinations were used (i) a combination of two IOPAs and (ii) a combination of PR and IOPA (−20°). Tube-shift localization technique was applied to both these combinations to derive the relation between third molar and IAN canal as "in contact," "separate," "buccal," "lingual," and "in line with the apex" and the results were compared with CT images. Statistical Analysis: Sensitivity, specificity, positive predictive value (PPV), and negative predictive value (NPV) were calculated using SPSS software version 15.0. Results: The combination of PR and IOPA radiographs showed 14 teeth to be in contact with IAN. This gave a sensitivity of 100%, specificity of 94.1%, PPV of 92.9%, and a NPV of 100% in determining the relation as "in contact" or "separate." 78.3%, 85.7%, 94.7%, and 54.5% were the sensitivity, specificity, PPV, and NPV in localizing it as "buccal," "lingual," or "in line with apex." These results were better than that of the combination of the two IOPAs. Conclusions: Localization using PR and IOPA could better deduce the relation between IAN and mandibular third molar.